2019
DOI: 10.1080/17441692.2019.1614645
|View full text |Cite
|
Sign up to set email alerts
|

Health system preparedness for emerging infectious diseases: A synthesis of the literature

Abstract: This review reflects on what the literature to date has taught us about how health systems of low-and middle-income countries (LMICs) respond to emerging infectious disease (EID) outbreaks. These findings are then applied to propose a conceptual framework characterising an EID prepared health system. A narrative synthesis approach was adopted to explore the key elements of LMIC health systems during an EID outbreak. Overarching themes ('core health system constructs') and sub-themes ('elements') relevant to EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 73 publications
1
58
0
Order By: Relevance
“…The number of cases in this study were, likewise, predicted by healthcare resources and expenditures, indicating that health systems with substantial amount of investment and health workers are essential in tackling the early spread of the disease. As there are currently no pharmaceutical interventions available, this may link to the availability of appropriate PPE amongst healthcare professions and the capacity to conduct testingboth of which are likely to be correlated with healthcare resources and expenditures (Chang et al, 2019;Goenka & Liu, 2019;Palagyi et al, 2019). Interestingly, we found that countries with a higher incidence of tuberculosis had a lower IRR for COVID-19 cases at 5, 10 and 15 days.…”
Section: Discussionmentioning
confidence: 81%
“…The number of cases in this study were, likewise, predicted by healthcare resources and expenditures, indicating that health systems with substantial amount of investment and health workers are essential in tackling the early spread of the disease. As there are currently no pharmaceutical interventions available, this may link to the availability of appropriate PPE amongst healthcare professions and the capacity to conduct testingboth of which are likely to be correlated with healthcare resources and expenditures (Chang et al, 2019;Goenka & Liu, 2019;Palagyi et al, 2019). Interestingly, we found that countries with a higher incidence of tuberculosis had a lower IRR for COVID-19 cases at 5, 10 and 15 days.…”
Section: Discussionmentioning
confidence: 81%
“…This lack of consistency between epidemiological curves and public health measures has thus sometimes led to scepticism about the very existence of COVID-19, as was sometimes the case with Ebola [31]. However, anticipation and preparation are precisely at the heart of epidemic management as the case of Ebola has clearly shown in the region [32] and trust and governance are essential elements of good pandemic preparedness [32].…”
Section: Discussionmentioning
confidence: 99%
“…Describing approaches falling under six predefined domains, 33 articles specifically focused on preparedness strategies of healthcare resources for the pandemic ( Table 1 ). 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 The final list of selected publications included 3 original articles, 9 commentaries, and 21 review articles. All but six articles were published between 2019 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…During the public health crisis, central-local cooperative governance should be created for developing an integrated and coordinated approach based on the regional centered healthcare system. 41 43 A decentralized healthcare system is favorable even in case of simultaneous local or regional epidemics. Subnational governments composed of regions and municipalities should be responsible for critical aspects of containment measures and health care, placing them at the frontline of crisis management.…”
Section: Discussionmentioning
confidence: 99%